PENERAPAN MEDIA FLIPBOOK INTERAKTIF BERMUATAN GAMIFIKASI UNTUK MATERI FOTOSINTESIS DAN PERKEMBANGBIAKAN TUMBUHAN PADA SISWA KELAS IV - Makhsushoh, Hikmatul; Wiratama, Novialita Angga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in primary school contributes a crucial role in shaping students' foundational knowledge and skills. As technology continues to advance, learning media are expected to respond to current societal needs. One of the main challenges in education is creating learning experiences that foster student interest and engagement, particularly in subjects like Science and Social Studies (IPAS), which are often perceived as less appealing. To deal with this situation, there is a requirement for learning media that are both effective and engaging. This study is conducted to explore the effectiveness of implementing an interactive flipbook integrated with gamification elements to enhance The educational performance of learners in grade four elementary students in Lamongan. The interactive flipbook is a digital e-book that mimics a physical book, enhanced with multimedia elements such as animations, videos, and audio, along with gamified features like interactive quizzes at the end of each lesson. The type of research applied in this study is a Pre-Experimental Design using a One-Group Pretest-Posttest Design model,and data were analyzed using the Normalized-Gain formula based on the results of pretest and posttest assessments. The findings reveal a noteworthy improvement in student learning outcomes. The average pretest score was 48.42, which increased to 89.73 on the posttest. The results suggest that the use of gamified interactive flipbooks is not only Successful in delivering learning content but also significantly boosts student motivation and achievement, offering a more engaging and enjoyable learning experience.